BT-7 Long-term outcome and late adverse effects of intracranial primary germ cell tumor. (6th December 2021) - Hanihara, Mitsuto; Kawataki, Tomoyuki; Saito, Ryu; Ogiwara, Masakazu; Kinouchi, Hiroyuki
Abstract: Background: Current standard of care for intracranial germ cell tumor (IGCT) have favorable cure rates. However, long-term treatment-related adverse event data are limited. The present study examined the long-term outcome of IGCT.Methods: The data from 27 patients with IGCT treated at our institutes from 1993 to 2020 were retrospectively analyzed. The patients were divided into two groups: group A; who received whole-ventricle RT (30 Gy) or focal RT (40-50Gy) from 1993 to 2012, group B; who received whole-ventricle RT (23.4 Gy) from 2013 to 2020. Complications and physical-activity level after treatment were retrospectively analyzed.Results: Pathological diagnosis was germinoma in all cases, and chemotherapy was CARE in 19 cases and ICE in 2 cases. Radiation therapy was performed in 15 cases in group A and 6 cases in group B. The follow-up period was 8–19 years (mean 11.3 years) in group A and 0.4–7 years (mean 3.6 years) in group B. Radiological cure was obtained in all cases, there was no recurrence. Hypopituitarism requiring hormone replacement therapy was observed in 53% of patients in group A and 50% of patients in group B. Late complications were cerebral hemorrhage from venous malformation (4 years after treatment), symptomatic cerebral atrophy in 2 cases (3 years / 6 years after treatment), radiation induced malignant glioma (19 years after treatment) in group A. The rate of good physical-activity was 71% of group A and 100% of group B.Discussion/Conclusions: CARE + whole-ventricle radiation therapy is appropriate as a standard treatment for ICGT. Late complications are directly linked to poor quality of life and may be radiation dose dependent. Optimize radiation therapy to further improve outcomes is required.